Semantik dan netnografi sebagai pendekatan penelitian untuk perancangan kembali (redesign) sebuah produk - Sumartono Sumartono (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2018)
This article discusses three research approaches that can be used as a basis for redesigning a product. These three approaches are not all related because netnography is usually associated with ethnography, a well-known approach in anthropology. Although some of the examples given here are rather simple, in its limitations, it is expected that this article is useful for those who want to use these three approaches to redesigning a product. Key words: netnografi, semantic, redesign